Pengaruh Fee Audit, Tenure Audit, Rotasi Audit Terhadap Kualitas Audit dengan Komite Audit Sebagai Variabel Moderasi pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia - Nur Isra Laili (Fakultas Ekonomi dan Bisnis, Universitas Catur Insan Cendekia, 2021)
This test aims to test the effect of audit fees, audit tenure, audit rotation on audit quality with the audit committee as a moderating variable (empirical studies on financial sector companies listed on the Indonesia stock exchange for the financial sector 2012-2016) The population in this study was 71 companies. The sampling technique used was purposive sampling and the number of samples was 23 companies. The model used in this study is Moderated Regression Analysis using panel data and processed using the Eviews 9.5 application. Results: Audit fees have a positive and insignificant effect on audit quality, audit tenure has a negative and insignificant effect on audit quality, audit rotation has a positive and significant effect. on the quality of the audit. The audit committee has a positive and significant effect on the relationship between audit fees and audit quality, the audit committee has a negative and insignificant effect on the relationship between audit tenure and audit quality, the audit committee has a positive and insignificant effect on the relationship between audit rotation and audit quality. This shows that the audit committee only mediates the relationship between the audit fee variable and audit quality.